A high-strength galvanized steel resistant to liquid metal embrittlement and a preparation method and application thereof

CN122979766APending Publication Date: 2026-10-27SHOUGANG GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611393570.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-09
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

但较高的铝含量会降低镀层熔点,增加点焊时液态金属的含量,反而可能加剧液态金属致脆风险,并损害焊接性能

Benefits of technology

本申请实施例提供了一种抗液态金属脆性的镀锌高强钢及制备方法和应用,以质量分数计,所述镀锌高强钢的化学成分为:C:0.05%~0.60%,Al:0.08%~3.00%,Si:0.10%~1.75%,Mn:1.0%~5.0%,Cr:0.20%~1.65%,Nb:0.01%~1.05%,P≤0.02%,S≤0.007%,N≤0.006%,Cu:0.01%~0.06%,B:0.001%~0.003%,其余为Fe及不可避免的杂质;其中,所述Al与所述Si的质量分数比值为0.9~4.0。通过对Al元素和Si元素的质量分数以及Al与Si的质量配比进行协同调控,并将Al与Si质量分数的比值精确控制在0.9~4.0的范围内,可以从材料本质上构建抵抗液态金属致脆(LME)的多重防线。提高Al的质量分数会增强铝元素在原子尺度上的排锌能力:铝原子能够更有效地阻碍液态锌在焊接高温下向钢基体晶界的渗透与扩散,从而从源头上减少液态金属入侵的驱动力。同时,适度降低Si的质量分数有助于减少镀锌高强钢表面在退火和镀锌过程中形成的硅氧化物,进而获得更均匀、致密且附着力更强的锌镀层,削弱因镀层质量不佳而诱发裂纹的起点。此外,优化的Al与Si质量配比还能通过Al与Si元素间的交互作用,抑制Cr和Mn等合金元素向晶界的过度偏聚与扩散,有效降低脆性内氧化物的生成倾向。较高的Al质量分数亦有助于调控镀锌高强钢的相变过程,减少最终微观组织中对液态锌脆化尤为敏感的残余奥氏体含量以及残余奥氏体在晶界的分布。上述多重机制共同作用,旨在全面提升镀锌高强钢在电阻点焊恶劣热-力耦合环境下的固有抗力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979766A_ABST
    Figure CN122979766A_ABST
Patent Text Reader

Abstract

The application relates to a zinc-plated high-strength steel with liquid metal embrittlement resistance, a preparation method and application, and belongs to the technical field of material processing. The chemical composition of the zinc-plated high-strength steel is as follows in terms of mass fraction: C: 0.05%-0.60%, Al: 0.08%-3.00%, Si: 0.10%-1.75%, Mn: 1.0%-5.0%, Cr: 0.20%-1.65%, Nb: 0.01%-1.05%, P<=0.02%, S<=0.007%, N<=0.006%, Cu: 0.01%-0.06%, B: 0.001%-0.003%, and the rest is Fe and inevitable impurities; wherein the mass ratio of the Al to the Si is 0.9-4.0. By optimizing the mass ratio of the Al to the Si, the liquid metal embrittlement crack tendency of the zinc-plated high-strength steel caused by zinc layer melting during resistance spot welding is significantly reduced. The preparation method of the zinc-plated high-strength steel comprises the following procedures: hot rolling, pickling, cold rolling, hot galvanizing and subsequent heat treatment under specific conditions. The obtained zinc-plated high-strength steel has high strength and excellent liquid metal embrittlement resistance, and is particularly suitable for resistance spot welding connection in automobile body manufacturing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of materials processing technology, and in particular to a galvanized high-strength steel resistant to liquid metal brittleness, its preparation method, and its application. Background Technology

[0002] To meet the demands of lightweight automotive manufacturing, high-strength steel has become the preferred material for key body components. Applying a galvanized layer to the surface of high-strength steel sheets utilizes the anodic protection of zinc to prevent corrosion of the high-strength steel substrate, thus significantly improving its corrosion resistance. In subsequent body assembly and manufacturing, resistance spot welding is the primary process for connecting body components.

[0003] However, during resistance spot welding, the temperature at the weld center is extremely high, while the melting point of zinc and zinc alloy coatings is relatively low. The high temperature causes the zinc and zinc alloy coatings to melt, and the molten zinc easily penetrates along the grain boundaries of the high-strength steel under welding stress. Simultaneously, the grain boundaries themselves exhibit a capillary adsorption effect on the liquid metal, which further exacerbates the penetration of liquid zinc, severely weakening the grain boundary bonding and ultimately inducing cracks known as liquid metal embrittlement (LME). Furthermore, the spot welding process involves complex tensile and compressive stress cycles, and the alternating stress generated by these cycles continuously promotes the initiation and propagation of LME cracks. LME cracking has become a prominent technical challenge affecting the welding reliability of galvanized high-strength steel.

[0004] To address the aforementioned problems, existing technologies have proposed several solutions. For example, one approach attempts to increase the local melting point and suppress cracking by precisely controlling welding process parameters, such as employing a specific current mode to alter the composition of the weld area. However, this process requires extremely stringent current control, is difficult to implement, and may affect the corrosion resistance of the weld area. Another technology focuses on the coating composition, developing aluminum-zinc-rich coatings to form a protective layer during hot forming. However, higher aluminum content lowers the coating melting point and increases the amount of liquid metal during spot welding, potentially exacerbating the risk of liquid metal embrittlement and impairing weld performance. Summary of the Invention

[0005] This application provides a galvanized high-strength steel resistant to liquid metal embrittlement, its preparation method, and its application, in order to solve the following technical problem: how to suppress liquid metal embrittlement cracks caused by the melting of the zinc layer during resistance spot welding of galvanized high-strength steel.

[0006] In a first aspect, embodiments of this application provide a galvanized high-strength steel resistant to liquid metal brittleness. The chemical composition of the galvanized high-strength steel, by mass fraction, is: C: 0.05%~0.60%, Al: 0.08%~3.00%, Si: 0.10%~1.75%, Mn: 1.0%~5.0%, Cr: 0.20%~1.65%, Nb: 0.01%~1.05%, P≤0.02%, S≤0.007%, N≤0.006%, Cu: 0.01%~0.06%, B: 0.001%~0.003%, with the remainder being Fe and unavoidable impurities. The mass fraction ratio of Al to Si is 0.9 to 4.0.

[0007] Optionally, by mass fraction, the mass fraction of C is 0.05%~0.40%, the mass fraction of Al is 0.40%~2.30%, and the mass fraction of Si is 0.20%~1.25%.

[0008] Optionally, the mass fraction ratio of Al to Si is 2.0 to 4.0.

[0009] Optionally, by volume fraction, the microstructure of the galvanized high-strength steel comprises ferrite: 10%~45%, martensite: 40%~70%, and retained austenite: 3%~12%.

[0010] Optionally, the galvanized high-strength steel surface has a hot-dip galvanized layer, and an Fe-Zn alloying layer is present between the hot-dip galvanized layer and the steel substrate.

[0011] Optionally, the galvanized high-strength steel meets at least one of the following properties: tensile strength ≥ 980 MPa, yield strength ≥ 700 MPa, and elongation after fracture A. 80 ≥12%.

[0012] Secondly, embodiments of this application provide a method for preparing the galvanized high-strength steel described in the first aspect, the method comprising: Molten steel with the following chemical composition is continuously cast to obtain a billet: C: 0.05%~0.60%, Al: 0.08%~3.00%, Si: 0.10%~1.75%, Mn: 1.0%~5.0%, Cr: 0.20%~1.65%, Nb: 0.01%~1.05%, P≤0.02%, S≤0.007%, N≤0.006%, Cu: 0.01%~0.06%, B: 0.001%~0.003%, with the remainder being Fe and unavoidable impurities; The billet is subjected to hot rolling, pickling, cold rolling and hot-dip galvanizing in sequence to obtain galvanized steel coil; The galvanized steel coil is heat-treated in a heat treatment furnace with a temperature of 70℃~350℃ and a dew point temperature of -55℃~-35℃ for 20min~60min, and then coiled to obtain galvanized high-strength steel.

[0013] Optionally, the temperature of the hot-dip galvanizing bath is 440℃~470℃, and the mass fraction of Al in the bath is 0.005%~0.35%.

[0014] Thirdly, embodiments of this application provide an application of the galvanized high-strength steel described in the first aspect, wherein the galvanized high-strength steel is used for resistance spot welding connections of automotive body structural components.

[0015] Optionally, the welding current of the resistance spot welding is 8kA~12kA, the welding time is 200ms~400ms, and the electrode pressure is 3kN~5kN.

[0016] The technical solutions provided in this application have the following advantages compared with the prior art: This application provides a galvanized high-strength steel resistant to liquid metal brittleness, its preparation method, and its application. The chemical composition of the galvanized high-strength steel, by mass fraction, is: C: 0.05%~0.60%, Al: 0.08%~3.00%, Si: 0.10%~1.75%, Mn: 1.0%~5.0%, Cr: 0.20%~1.65%, Nb: 0.01%~1.05%, P≤0.02%, S≤0.007%, N≤0.006%, Cu: 0.01%~0.06%, B: 0.001%~0.003%, with the remainder being Fe and unavoidable impurities; wherein the mass fraction ratio of Al to Si is 0.9~4.0. By synergistically controlling the mass fractions of Al and Si, as well as the mass ratio of Al to Si, and precisely managing the Al / Si mass fraction ratio within the range of 0.9 to 4.0, multiple lines of defense against liquid metal embrittlement (LME) can be constructed from the material's inherent nature. Increasing the Al mass fraction enhances the aluminum's ability to remove zinc at the atomic scale: aluminum atoms can more effectively hinder the penetration and diffusion of liquid zinc into the steel matrix grain boundaries at the high welding temperatures, thereby reducing the driving force for liquid metal intrusion at its source. Simultaneously, moderately reducing the Si mass fraction helps reduce the formation of silicon oxides on the surface of galvanized high-strength steel during annealing and galvanizing, resulting in a more uniform, dense, and strongly adhered zinc coating, thus weakening the initiation point of cracks induced by poor coating quality. Furthermore, the optimized Al / Si mass ratio can also suppress the excessive segregation and diffusion of alloying elements such as Cr and Mn to grain boundaries through the interaction between Al and Si, effectively reducing the tendency for the formation of brittle internal oxides. A higher Al mass fraction also helps to regulate the phase transformation process of galvanized high-strength steel, reducing the content of retained austenite, which is particularly sensitive to liquid zinc embrittlement, and the distribution of retained austenite at grain boundaries in the final microstructure. These multiple mechanisms work together to comprehensively enhance the inherent resistance of galvanized high-strength steel to the harsh thermo-mechanical coupling environment of resistance spot welding.

[0017] In summary, by systematically designing and limiting the absolute mass fractions and relative proportions of the key elements Al and Si, comprehensive optimization of zinc layer wetting behavior, coating interface quality, grain boundary chemical composition, and microstructure was simultaneously achieved. This fundamentally altered the interaction between galvanized high-strength steel and molten zinc, significantly suppressing the penetration and embrittlement process of liquid zinc along grain boundaries. Without compromising the basic strength of galvanized high-strength steel, this composition design effectively solved the problem of liquid metal embrittlement cracking caused by zinc layer melting during resistance spot welding of galvanized high-strength steel, providing a material solution for lightweight automotive manufacturing that combines high strength and high weldability. Attached Figure Description

[0018] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.

[0019] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, those skilled in the art can obtain other drawings based on these drawings without any creative effort.

[0020] Figure 1 A flowchart illustrating a method for preparing galvanized high-strength steel resistant to liquid metal brittleness, as provided in this application embodiment; Figure 2 A macroscopic morphology diagram of a resistance spot weld cross-section of galvanized high-strength steel resistant to liquid metal brittleness, provided for an embodiment of this application; Figure 3 A schematic diagram illustrating four types of LME crack classification in resistance spot welds of galvanized high-strength steel resistant to liquid metal brittleness, provided for embodiments of this application; Figure 4 This application provides a comparison of LME microcrack size distribution in galvanized high-strength steel samples with different Al / Si ratios that resist liquid metal brittleness, as an embodiment of the present application. Figure 5 A scanning electron microscope (SEM) image of the LME crack in a resistance spot weld of galvanized high-strength steel that is resistant to liquid metal brittleness, provided in Embodiment 1 of this application. Figure 6 This is a scanning electron microscope (SEM) image of the LME crack in a resistance spot weld of galvanized high-strength steel that is resistant to liquid metal brittleness, provided in Embodiment 2 of this application. Figure 7 A scanning electron microscope (SEM) image of an LME crack in a resistance spot weld of galvanized high-strength steel, provided as Comparative Example 1 of this application. Figure 8 The image provided in Comparative Example 2 of this application shows the LME crack morphology of a resistance spot weld on galvanized high-strength steel. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some, not all, of the embodiments of this application. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application.

[0022] The range descriptions used herein, such as numerical ranges and proportional ranges, include all possible sub-ranges and single numerical values ​​within that range. For example, the range descriptions of "1 to 6" or "1~6" cover all sub-ranges between 1 and 6 (such as 1 to 3, 2 to 5, etc.) and single numbers (such as 1, 2, 3, 4, 5, 6). Unless otherwise specified, the terms "including" and "contains" used herein mean "including but not limited to"; relational terms such as "first" and "second" are used only to distinguish different entities or operations and do not imply an actual order or relationship. "And / or" indicates that multiple situations can exist individually or simultaneously. Expressions such as "at least one," "multiple," and "at least one" refer to any combination of the corresponding objects, including combinations of single or multiple objects. The proportional relationships mentioned herein, such as mass ratios and molar ratios, should be understood as the correspondence between the first and second terms of a proportional formula, according to the order of description. The raw materials, reagents, instruments, and equipment used herein can all be obtained through commercial purchase or prepared using existing methods.

[0023] In a first aspect, embodiments of this application provide a galvanized high-strength steel resistant to liquid metal brittleness. The chemical composition of the galvanized high-strength steel, by mass fraction, is: C: 0.05%~0.60%, Al: 0.08%~3.00%, Si: 0.10%~1.75%, Mn: 1.0%~5.0%, Cr: 0.20%~1.65%, Nb: 0.01%~1.05%, P≤0.02%, S≤0.007%, N≤0.006%, Cu: 0.01%~0.06%, B: 0.001%~0.003%, with the remainder being Fe and unavoidable impurities. The mass fraction ratio of Al to Si is 0.9 to 4.0.

[0024] In some embodiments, the mass fraction of C is 0.05% to 0.40%, the mass fraction of Al is 0.40% to 2.30%, and the mass fraction of Si is 0.20% to 1.25%.

[0025] In some embodiments, the mass fraction ratio of Al to Si is 2.0 to 4.0.

[0026] The positive effects of limiting the C mass fraction to 0.05%~0.60% include: C provides necessary solid solution strengthening and phase transformation strengthening in the matrix, ensuring that galvanized high-strength steel achieves a tensile strength higher than 980 MPa and a yield strength higher than 700 MPa, providing a mechanical basis for lightweight components. A C mass fraction within the specified range is a prerequisite for maintaining the formation of strengthening phases such as martensite in galvanized high-strength steel. When the C mass fraction is too high, it will impair the weldability and plasticity of galvanized high-strength steel. Therefore, controlling the C mass fraction within the specified range can ensure the strength of galvanized high-strength steel while avoiding the risk of brittleness. Preferably, the C mass fraction is 0.05%~0.40%. Examples of C mass fractions include 0.05%, 0.20%, 0.35%, and 0.50%.

[0027] The positive effects of limiting the Al mass fraction to 0.08%~3.00% include: increasing the Al mass fraction enhances the matrix's repulsion of liquid zinc at the atomic scale, effectively preventing the penetration and diffusion of molten zinc to grain boundaries. Simultaneously, a higher Al mass fraction helps reduce the content of retained austenite in the microstructure, which is sensitive to liquid zinc corrosion, thus fundamentally improving the crack resistance of galvanized high-strength steel. Preferably, the Al mass fraction is 0.40%~2.30%. Exemplary examples include Al mass fractions of 0.50%, 1.00%, 1.50%, 2.00%, 2.50%, and 3.00%.

[0028] The positive effects of limiting the Si mass fraction to 0.10%~1.75% are as follows: Lowering the Si mass fraction can reduce the formation of silicon oxides on the surface of galvanized high-strength steel during annealing and galvanizing, thereby improving the uniformity, adhesion quality, and continuity of the galvanized layer. Preferably, the Si mass fraction is 0.20%~1.25%. For example, the Si mass fraction can be 0.50%, 1.00%, 1.50%, etc.

[0029] The positive effects of limiting the Mn mass fraction to 1.0%~5.0%: Mn provides a significant solid solution strengthening effect for galvanized high-strength steel, ensuring that the galvanized high-strength steel achieves a strength higher than 980 MPa. An appropriate Mn mass fraction helps galvanized high-strength steel obtain a multiphase microstructure containing martensite and a suitable amount of retained austenite after heat treatment. This multiphase microstructure is a prerequisite for the good comprehensive properties of galvanized high-strength steel. For example, the Mn mass fraction can be 1.0%, 2.0%, 3.0%, 4.0%, 5.0%, etc.

[0030] The positive effects of limiting the Cr mass fraction to 0.20%~1.65% include: Cr further strengthens the galvanized high-strength steel through solid solution strengthening and improves its hardenability. Controlling the Cr mass fraction within the specified range can effectively suppress excessive Cr segregation and diffusion at grain boundaries. For example, the Cr mass fraction can be 0.50%, 1.00%, 1.50%, etc.

[0031] The positive effects of limiting the Nb mass fraction to 0.01%~1.05% include: utilizing the microalloying effect of Nb, it can form fine carbonitrides, which inhibit austenite grain growth during hot rolling, thereby refining the final microstructure grains. For example, the Nb mass fraction can be 0.05%, 0.25%, 0.45%, 0.65%, 0.85%, 1.05%, etc.

[0032] The positive effects of limiting the mass fraction of phosphorus (P) to ≤0.02% include: controlling the mass fraction of P within a low range helps maintain the purity and toughness of grain boundaries, thereby fundamentally improving the ability of grain boundaries to resist liquid zinc penetration and crack propagation. For example, the mass fraction of P can be 0.01%, 0.02%, etc.

[0033] The positive effects of limiting the sulfur (S) mass fraction to ≤0.007% include minimizing the quantity and size of sulfide inclusions in galvanized high-strength steel. Sulfide inclusions, especially MnS, tend to elongate along the rolling direction during rolling, thus becoming stress concentration points and crack initiation sites. Under the complex stress field of resistance spot welding, these sulfide inclusions promote crack nucleation. Reducing the S mass fraction effectively reduces these harmful inclusions, thereby weakening the crack initiation point and improving the overall crack resistance of galvanized high-strength steel. For example, the S mass fraction can be 0.001%, 0.003%, 0.005%, 0.007%, etc.

[0034] The positive effects of limiting the N mass fraction to ≤0.006%: The main purpose of controlling the N mass fraction is to avoid the formation of coarse nitrides or carbonitrides. Excessively high N mass fractions can lead to the precipitation of brittle phases at grain boundaries or within grains. These precipitates can disrupt the continuity of the matrix and cause stress concentration. Under the combined effects of liquid zinc corrosion and welding stress, these brittle phases may become preferred nucleation sites for cracks. Controlling the N mass fraction helps maintain the homogeneity of the microstructure and reduces the tendency for embrittlement due to second phases. For example, the N mass fraction can be 0.002%, 0.004%, 0.006%, etc.

[0035] The positive effects of limiting the mass fraction of Cu to 0.01%~0.06% are as follows: A trace amount of Cu can thermodynamically promote the formation of a denser and thinner oxide layer on the surface of galvanized high-strength steel. This oxide layer is beneficial for obtaining a zinc coating with better adhesion and continuity during subsequent hot-dip galvanizing. For example, the mass fraction of Cu can be 0.02%, 0.04%, 0.06%, etc.

[0036] The positive effects of limiting the mass fraction of boron (B) to 0.001%~0.003% include: utilizing the strong grain boundary segregation properties of B, boron atoms can adsorb onto austenite grain boundaries and fill defects such as vacancies, thereby significantly strengthening the grain boundaries. For example, the mass fraction of B can be 0.001%, 0.002%, 0.003%, etc.

[0037] Fe is a matrix element, and the specific content / range of Fe can be obtained through the upper and lower limit formulas of the component, that is: The sum of the percentages of all components in a composition should equal 100%, and the content ranges of several components should meet the following conditions: the upper limit of a certain component + the lower limit of other components ≤ 100; the lower limit of a certain component + the upper limit of other components ≥ 100. Furthermore, the specific content of Fe is made up to 100% by the actual detected values ​​of the other chemical components mentioned above, together with any unlisted active elements and / or impurity elements, and Fe must constitute the absolute proportion as a matrix element.

[0038] The mass fraction ratio of Al to Si is 0.9 to 4.0. By synergistically controlling this key element ratio, the crack resistance of galvanized high-strength steel is fundamentally improved. Increasing the mass fraction of Al enhances its zinc-removing effect at the atomic scale, effectively inhibiting the penetration and diffusion of liquid zinc to grain boundaries at high welding temperatures. Simultaneously, reducing the mass fraction of Si helps reduce the formation of surface silicon oxides, thereby improving the uniformity and bonding quality of the galvanized layer and weakening the initiation point of cracks. Preferably, the mass fraction ratio of Al to Si is 2.0 to 4.0. Exemplary examples include mass fraction ratios of 1.0, 2.0, 3.0, and 4.0.

[0039] In some embodiments, the microstructure of the galvanized high-strength steel, by volume fraction, comprises: ferrite: 10%~45%, martensite: 40%~70%, and retained austenite: 3%~12%.

[0040] Ferrite, as a soft and ductile phase, effectively buffers and disperses localized stresses generated during welding, delaying crack initiation. Martensite provides the necessary high matrix strength, ensuring the components meet the mechanical properties required for lightweight construction. The content and distribution of retained austenite, sensitive to liquid zinc corrosion, are strictly controlled. By optimizing the aluminum-to-silicon mass fraction ratio within the range of 2.0–4.0, combined with specific heat treatment processes, the volume fraction and stability of retained austenite can be effectively controlled, reducing the continuous distribution of retained austenite at grain boundaries, thereby significantly weakening the path of liquid zinc penetration along grain boundaries and initiating brittle fracture. For example, the volume fraction of ferrite can be 10%, 25%, 40%, etc.; the volume fraction of martensite can be 40%, 50%, 60%, 70%, etc.; and the volume fraction of retained austenite can be 3%, 7%, 11%, etc.

[0041] Methods for determining the volume fraction of retained austenite include: The determination is performed using either electron backscatter diffraction (EBSD) or X-ray diffraction (XRD). EBSD is preferred, and the specific steps are as follows: (1) Sample preparation: A sample with a size of 10mm×10mm×3mm was cut from the middle of the heat-treated galvanized steel coil. After mechanical grinding and polishing, the surface stress layer was removed by electrolytic polishing (electrolyte is 10% perchloric acid alcohol solution, voltage 20V, temperature -20℃, time 60s). (2) EBSD scanning: EBSD scanning was performed in a scanning electron microscope (SEM) with an accelerating voltage of 20kV, a working distance of 15mm, a step size of 0.1μm, and a scanning area of ​​not less than 200μm×200μm; (3) Data processing: Channel 5 or OIM Analysis software was used to calibrate Kikuchi patterns with a calibration rate of not less than 90%. Ferrite (body-centered cubic, BCC), martensite (body-centered cubic, BCC, high dislocation density) and retained austenite (face-centered cubic, FCC) were distinguished by phase identification function. The area fraction of each phase was calculated and approximated as the volume fraction. (4) Measurement location: Three fields of view are measured at 1 / 4 and 1 / 2 of the thickness direction of the steel plate, and the average value is taken as the residual austenite volume fraction of the sample.

[0042] Retained austenite is highly sensitive to liquid metal embrittlement (LME), and an excessively high volume fraction of retained austenite significantly increases the tendency for LME crack initiation. This application optimizes the Al to Si mass fraction ratio to 0.9–4.0, and, in conjunction with subsequent heat treatment processes, controls the retained austenite volume fraction within the range of 3%–12%, effectively reducing LME susceptibility while ensuring good strength and plasticity of the steel sheet.

[0043] In some embodiments, the galvanized high-strength steel surface has a hot-dip galvanized layer, and an Fe-Zn alloying layer is present between the hot-dip galvanized layer and the steel substrate.

[0044] Formation mechanism of Fe-Zn alloy layer: During the heat treatment process following hot-dip galvanizing (temperature 70℃~350℃, dew point temperature -55℃~-35℃), a solid-state diffusion reaction occurs at the interface between the galvanized layer and the steel substrate, forming an Fe-Zn intermetallic compound layer, namely the Fe-Zn alloy layer. The formation process of this alloy layer is as follows: (1) Diffusion stage: At the heat treatment temperature, Fe atoms in the steel substrate diffuse toward the zinc plating layer, while Zn atoms in the zinc plating layer diffuse toward the steel substrate, forming a concentration gradient at the interface; (2) Reaction stage: When the atomic concentrations of Fe and Zn reach the stoichiometric ratio, a reaction occurs to form Fe-Zn intermetallic compounds, mainly including the ζ phase (FeZn). 13 ), δ1 phase (FeZn7) and Γ phase (Fe3Zn) 10 ); (3) Growth stage: As the heat treatment time increases, the thickness of the alloy layer gradually increases. However, when the temperature is controlled within the range of 70℃~350℃, the growth rate of the alloy layer is slow, forming a thin and dense alloy layer with a thickness of 0.5μm~3.0μm.

[0045] The melting point of the Fe-Zn alloy layer (approximately 530℃~780℃) is significantly higher than that of the pure zinc coating (419.5℃). During subsequent resistance spot welding, the alloy layer can slow down the melting rate of the coating and reduce the total amount of liquid zinc that can penetrate to the grain boundaries, thereby reducing the tendency for LME crack initiation from the source. At the same time, the dense alloy layer can also improve the bonding strength between the coating and the substrate, preventing premature peeling of the coating under welding stress.

[0046] Characterization methods for Fe-Zn alloyed layers: Cross-sectional morphology and elemental distribution analysis were performed using scanning electron microscopy (SEM) with energy dispersive spectroscopy (EDS). After mounting, grinding, and polishing, the samples were lightly etched with a 4% nitric acid-alcohol solution for 5–10 seconds. The cross-sectional morphology of the alloyed layer was observed under SEM, and its thickness was measured. The distribution of Fe and Zn elements at the interface was confirmed by EDS line or area scanning analysis, confirming the presence of Fe-Zn intermetallic compounds.

[0047] In some embodiments, the galvanized high-strength steel satisfies at least one of the following properties: tensile strength ≥ 980 MPa, yield strength ≥ 700 MPa, and elongation after fracture A. 80 ≥12%.

[0048] Tensile strength: The maximum stress a material can withstand in a tensile test. A tensile strength ≥ 980 MPa ensures that this galvanized high-strength steel possesses the high load-bearing capacity and resistance to overall fracture necessary for automotive structural components. Examples of tensile strengths include 980 MPa, 1000 MPa, and 1020 MPa. Yield strength: The stress threshold at which a material begins to undergo significant plastic deformation. A yield strength ≥ 700 MPa means that this galvanized high-strength steel has a high elastic limit under complex welding stress fields, effectively resisting premature plastic deformation caused by welding thermal cycles and external loads, providing crucial support for maintaining the macroscopic integrity of the structure in the weld area under liquid metal erosion. Examples of yield strengths include 700 MPa, 720 MPa, and 740 MPa. Elongation after fracture A 80 Elongation after fracture (A): Percentage of elongation after tensile fracture for a specimen with a gauge length of 80 mm. 80 ≥12% indicates that galvanized high-strength steel possesses good uniform plastic deformation capability. For example, the elongation after fracture A... 80 It can be 12%, 14%, 16%, etc.

[0049] Figure 1 This is a flowchart illustrating a method for preparing galvanized high-strength steel resistant to liquid metal brittleness, as provided in an embodiment of this application.

[0050] Please see Figure 1 Secondly, this application provides a method for preparing the galvanized high-strength steel described in the first aspect, the method comprising: S1. Continuously cast molten steel having the following chemical composition to obtain a billet: C: 0.05%~0.60%, Al: 0.08%~3.00%, Si: 0.10%~1.75%, Mn: 1.0%~5.0%, Cr: 0.20%~1.65%, Nb: 0.01%~1.05%, P≤0.02%, S≤0.007%, N≤0.006%, Cu: 0.01%~0.06%, B: 0.001%~0.003%, with the remainder being Fe and unavoidable impurities; S2. The billet is subjected to hot rolling, pickling, cold rolling and hot-dip galvanizing in sequence to obtain galvanized steel coil; S3. The galvanized steel coil is heat-treated in a heat treatment furnace with a temperature of 70℃~350℃ and a dew point temperature of -55℃~-35℃ for 20min~60min, and then coiled to obtain galvanized high-strength steel.

[0051] In some embodiments, the temperature of the hot-dip galvanizing bath is 440°C to 470°C, and the mass fraction of Al in the bath is 0.005% to 0.35%.

[0052] Synergistic effect of Al content in plating solution and Al / Si ratio in substrate: In the hot-dip galvanizing process of this application, the bath temperature is 440℃~470℃, and the mass fraction of Al in the bath is 0.005%~0.35%. This mass fraction of Al in the bath synergistically enhances the LME resistance of the galvanized high-strength steel with the Al / Si ratio in the steel substrate. (1) The trace amount of Al in the plating solution can form a continuous Fe2Al5 inhibition layer at the interface between the coating and the steel substrate. This inhibition layer is dense and has high thermal stability, which can hinder the direct diffusion of Zn atoms into the steel substrate and reduce the interfacial reaction rate. (2) The high Al mass fraction in the steel substrate (Al / Si ratio 0.9~4.0) causes trace amounts of Al2O3 to form on the substrate surface during annealing. This oxide layer works synergistically with Al in the plating solution to enhance interfacial bonding and reduce peeling of the coating during welding. (3) The synergistic effect of the substrate Al and the plating solution Al can also regulate the growth kinetics of the alloy layer, so that the thickness of the alloy layer is kept in the optimal range of 0.5μm~3.0μm, which not only ensures the corrosion resistance of the coating, but also avoids the embrittlement problem caused by excessively thick alloy layer.

[0053] If the Al mass fraction in the plating bath is too high (>0.35%), it will lower the melting point of the coating and increase the total amount of liquid metal during welding, thus exacerbating the risk of LME (Liquid Metal Erosion). If the Al mass fraction in the plating bath is too low (<0.005%), an effective Fe2Al5 inhibition layer cannot be formed, resulting in a decrease in both the corrosion resistance and weldability of the coating. Therefore, controlling the Al mass fraction in the plating bath within the range of 0.005% to 0.35% creates the best synergistic effect with the Al / Si ratio of the substrate of 0.9 to 4.0. For example, the plating bath temperature for hot-dip galvanizing can be 440℃, 450℃, 460℃, 470℃, etc.; the Al mass fraction in the plating bath can be 0.05%, 0.20%, 0.35%, etc.

[0054] In some embodiments, the heat treatment temperature is 70°C to 350°C, and the heat treatment time is 20 min to 60 min.

[0055] The heat treatment temperature is between 70℃ and 350℃. This heat treatment promotes a moderate alloying reaction between the hot-dip galvanized layer and the steel substrate, forming a more stable Fe-Zn intermetallic compound layer. This alloyed layer has a higher melting point and thermal stability than pure zinc, thus more effectively suppressing premature and excessive melting of the coating under the localized high temperatures of subsequent resistance spot welding. This reduces the total amount of liquid zinc that can penetrate to the grain boundaries, directly contributing to reducing the tendency for embrittlement cracks in liquid metal. For example, the heat treatment temperature can be 100℃, 150℃, 200℃, 250℃, 300℃, or 350℃. The heat treatment time is between 20 min and 60 min. This time range ensures the formation of a continuous and dense alloyed structure, while avoiding insufficient reaction and coating instability due to too short a time, and excessive thickness and embrittlement due to too long a time. For example, the heat treatment time can be 20 min, 40 min, or 60 min.

[0056] In some embodiments, the dew point temperature inside the heat treatment furnace is -55°C to -35°C.

[0057] The dew point temperature inside the heat treatment furnace is between -55℃ and -35℃. This range of dew point temperatures is used to precisely control the humidity of the heat treatment environment, thereby effectively inhibiting the formation of excessive oxides on the surface of tin-plated high-strength steel during heat treatment. A lower dew point means an extremely dry ambient atmosphere, which significantly reduces the tendency for oxidation of the galvanized high-strength steel surface. For example, the dew point temperature inside the heat treatment furnace can be -55℃, -45℃, or -35℃.

[0058] Thirdly, embodiments of this application provide an application of the galvanized high-strength steel described in the first aspect, wherein the galvanized high-strength steel is used for resistance spot welding connections of automotive body structural components.

[0059] In some embodiments, the resistance spot welding current is 8kA~12kA, the welding time is 200ms~400ms, and the electrode pressure is 3kN~5kN.

[0060] The influence of resistance spot welding process parameters on LME cracking: In the application embodiments of this application, the galvanized high-strength steel is used for resistance spot welding connections of automotive body structural components. The welding current for resistance spot welding is 8kA~12kA, the welding time is 200ms~400ms, and the electrode pressure is 3kN~5kN. The selection of the above process parameters is closely related to the LME resistance performance of the galvanized high-strength steel. (1) Welding current (8kA~12kA): The welding current directly determines the peak temperature of the weld area. Too low a current (<8kA) will result in insufficient weld nugget size and reduced joint strength; too high a current (>12kA) will cause the weld center temperature to exceed 1100℃, exacerbating the amount of zinc melting and the penetration depth of liquid zinc. Controlling the current within the range of 8kA~12kA can maintain the weld center temperature at 950℃~1050℃, ensuring both nugget formation and controlling the total amount of liquid zinc.

[0061] (2) Welding time (200ms~400ms): Welding time affects the total heat input and the contact time of liquid zinc. Too short a time (<200ms) will result in insufficient heat input and incomplete fusion of the weld joint; too long a time (>400ms) will prolong the contact time between liquid zinc and grain boundaries, increasing the LME crack propagation length. Due to the optimized Al / Si ratio and low residual austenite content, the galvanized high-strength steel of this application can control the LME crack coefficient to below 80 within a welding time of 200ms~400ms.

[0062] (3) Electrode pressure (3kN~5kN): Electrode pressure affects the stress state of the weld joint area and the extrusion effect of the zinc layer. Too low a pressure (<3kN) will lead to excessive contact resistance and local overheating; too high a pressure (>5kN) will cause the electrode indentation to be too deep, weakening the effective load-bearing section of the steel plate. Within the pressure range of 3kN~5kN, the electrode can effectively extrude some molten zinc, reducing the amount of liquid zinc that can penetrate into the grain boundaries. At the same time, the tensile and compressive stress cycle amplitude in the weld joint area is moderate, which is beneficial to suppressing the propagation of LME cracks.

[0063] Under the optimized welding process parameters described above, the weld crack coefficient of the galvanized high-strength steel (Al / Si=3.25) in Example 1 of this application is 36.5, and the crack coefficient of Example 2 (Al / Si=2.25) is 79.8, both significantly lower than those of Comparative Example 1 (Al / Si=0.94, crack coefficient 152.3) and Comparative Example 2 (Al / Si=0.80, crack coefficient 269). This indicates that, through the synergistic control of matrix composition optimization (Al / Si ratio 0.9~4.0) and welding process parameters (current 8kA~12kA, time 200ms~400ms, pressure 3kN~5kN), this application can significantly suppress brittle cracking of liquid metal during resistance spot welding, ensuring the reliability of the welded joint.

[0064] The product prepared by the method for preparing galvanized high-strength steel is the aforementioned galvanized high-strength steel. Since the method for preparing galvanized high-strength steel adopts some or all of the technical solutions of the embodiments of galvanized high-strength steel, it has at least all the beneficial effects brought about by the technical solutions of the aforementioned embodiments, which will not be elaborated here.

[0065] The present application is further illustrated below with reference to specific embodiments. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to national standards / industry standards / the disclosure herein; if there are no corresponding national standards / industry standards / the disclosure herein, they are performed according to generally accepted international standards, conventional conditions, or conditions recommended by the manufacturer.

[0066] The chemical composition (mass percentage / %) of the examples and comparative examples is shown in Table 1.

[0067] Table 1

[0068] Based on the chemical composition of the embodiments and comparative examples, this embodiment also provides a method for preparing galvanized high-strength steel resistant to liquid metal brittleness, comprising the following steps: The molten steel with the chemical composition described in Table 1 was continuously cast to obtain a billet; The billet is subjected to hot rolling, pickling, cold rolling and hot-dip galvanizing in sequence to obtain galvanized steel coil; The galvanized steel coils are heat-treated and wound sequentially to obtain galvanized high-strength steel. Please refer to Table 2 for the preparation process parameters.

[0069] Table 2

[0070] To quantitatively evaluate the resistance to liquid metal embrittlement (LME) of galvanized high-strength steel during resistance spot welding, this application uses the crack index (CI) as an evaluation metric. The crack index is determined by evaluating the crack strength of the weld shoulder region (i.e., the weld shoulder area). Figure 3 The microcracks in the D-type crack initiation region shown in the figure were obtained through statistical calculations, and the specific definitions are as follows: The formula for calculating the crack coefficient (CI) is as follows: (1) In the formula: L i (1) : The length of the i-th crack, and satisfying L i (1) ≤50μm; L i (2) The length of the i-th crack, satisfying 50 μm. <L i (2) ≤100μm; L i (3) The length of the i-th crack, satisfying 100 μm. <L i (3) ≤200μm; t: Total thickness of the steel plate at the weld point, in μm; Coefficients 0.1, 1.0, and 10: These correspond to weighting coefficients for different length ranges, reflecting the degree of contribution of crack length to LME sensitivity. Statistical area: A ring-shaped area on the shoulder with a radius of 6mm, centered on the center of the solder joint; Crack count: 20 fields of view were counted for each sample, and the 3 longest cracks in each field of view were selected for the calculation.

[0071] The lower the crack coefficient (CI), the shorter the total length of LME cracks in the weld area, the lower the proportion of large-size cracks, and the better the material's resistance to liquid metal embrittlement. Based on the statistical results of the embodiments and comparative examples of this application, CI < 80 is considered low LME sensitivity, CI ≥ 80 and < 150 is considered medium LME sensitivity, and CI ≥ 150 is considered high LME sensitivity.

[0072] Table 3

[0073] The data tables above provide a clear comparison of the differences between various embodiments and comparative examples. The following conclusions can be drawn: As can be seen from the data in Table 3, the galvanized high-strength steel provided in the embodiments of this application has a crack coefficient of 36.5~779.8, low LME sensitivity, and excellent performance.

[0074] As shown in Examples 1-2 and Comparative Examples 1-2, the mass fraction ratios of Al to Si in Examples 1-2 were 3.25 and 2.25, respectively, with corresponding crack coefficients of 36.5 and 79.8, both at relatively low levels. This indicates that increasing the mass fraction ratio of Al to Si can effectively reduce the LME crack sensitivity of galvanized high-strength steel, reduce the proportion of liquid metal generated and penetrating into the matrix, and thus alleviate the microcracks in liquid metal generated during welding. In contrast, the Al to Si ratios in Comparative Examples 1-2 were 0.94 and 0.80, respectively, with corresponding crack coefficients as high as 152.3 and 269, indicating that a lower mass fraction ratio of Al to Si leads to a significant increase in crack sensitivity and exacerbates the tendency of liquid metal to become brittle.

[0075] To further clarify the influence of the Al / Si ratio on the microstructure, the residual austenite volume fraction of Examples 1, 2, 1, and 2 were determined in this application, and the results are shown in Table 4.

[0076] Table 4

[0077] Table 4 shows that the Al / Si ratio is negatively correlated with the volume fraction of retained austenite. When the Al / Si ratio is ≥0.9, the volume fraction of retained austenite can be controlled below 12%; when the Al / Si ratio is ≥2.0, the volume fraction of retained austenite can be further reduced to below 10%. Higher Al content can promote the transformation of austenite to ferrite and martensite, reducing the content of retained austenite that is stable at room temperature; simultaneously, Al increases the onset temperature (Mi) of the austenite-to-martensite transformation. s This allows more austenite to transform into martensite during the subsequent cooling process, thereby reducing the content of residual austenite that is sensitive to LME.

[0078] Appendix Figures 2-8 Detailed explanation: Figure 2 This is a macroscopic morphological image of a resistance spot weld cross-section of galvanized high-strength steel resistant to liquid metal brittleness, provided as an embodiment of this application. According to... Figure 2 It is known that after resistance spot welding, the tensile fracture of the brittle galvanized high-strength steel resistant to liquid metal occurs in the base region far from the weld point, and no premature cracking occurs in the weld point area. The entire gauge length exhibits uniform plastic deformation characteristics, indicating that this application effectively suppresses the initiation and propagation of brittle cracks caused by liquid metal in the weld point area through composition optimization design. The strength and toughness of the weld point itself meet the load-bearing requirements, and the welded joint has excellent reliability, which can match the mechanical performance requirements of the welded joint for automotive body structural components.

[0079] Figure 3 This is a schematic diagram illustrating four types of LME crack classification in resistance spot welds of galvanized high-strength steel resistant to liquid metal brittleness, provided as an embodiment of this application. According to... Figure 3 It can be seen that LME cracks in the resistance spot welding area of ​​galvanized high-strength steel are classified into four types according to their initiation location: Type A surface cracks located inside the 6mm electrode indentation, Type B surface cracks located outside the electrode indentation, Type C interface surface cracks located at the interface between the two steel plates of the weld, and Type D cracks located on the surface of the transition zone at the outer edge of the indentation. The boundaries of the different functional areas of the weld are also clearly marked. This clear classification provides a unified standard for subsequent statistical evaluation of the severity of LME cracking under different composition designs, and also intuitively shows the typical location of Type D LME cracks, facilitating subsequent targeted quantitative analysis of the actual effect of different Al / Si ratios on resisting liquid metal embrittlement cracking.

[0080] Figure 4 This application provides a comparison of LME microcrack size distributions in galvanized high-strength steel samples with different Al / Si ratios to resist liquid metal brittleness, as shown in the embodiments of this application. Figure 4It is known that the LME crack level of galvanized high-strength steel is negatively correlated with the Al / Si mass fraction ratio. A higher Al / Si mass fraction ratio results in a lower LME D-type crack index and a smaller overall crack size. When the Al / Si mass fraction ratio is controlled within the range required by this application, the corresponding LME D-type crack indices are only 36.5 and 79.8, with the length of the vast majority of cracks controlled at extremely low levels, indicating low embrittlement sensitivity of the liquid metal. When the Al / Si mass fraction ratio falls below the lower limit required by this application, the LME D-type crack index increases significantly with decreasing ratio, the number and proportion of long cracks increase significantly, and the embrittlement problem of the liquid metal is significantly exacerbated.

[0081] Figure 5 This is a scanning electron microscope (SEM) image of the LME crack morphology of a resistance spot weld on galvanized high-strength steel that resists liquid metal brittleness, provided in Embodiment 1 of this application. According to... Figure 5 It is known that the mass fraction ratio of Al to Si in the galvanized high-strength steel of Example 1 is 3.25, which meets the requirement of 0.9 to 4.0 set in this application. After resistance spot welding, only a very small number of small LME cracks exist in the weld area, and no large-area long cracks are initiated or extended. This directly proves that controlling the mass fraction ratio of Al to Si within the range required by this invention can effectively suppress liquid metal embrittlement cracks caused by liquid zinc penetration during the resistance spot welding of galvanized high-strength steel. Galvanized high-strength steel has excellent resistance to liquid metal embrittlement.

[0082] Figure 6 This is a scanning electron microscope (SEM) image of the LME crack morphology of a resistance spot weld joint in galvanized high-strength steel that resists liquid metal brittleness, provided in Embodiment 2 of this application. According to... Figure 6 It can be seen that the mass fraction ratio of Al to Si in the galvanized high-strength steel of Example 2 is 2.25, which meets the composition range requirement of 0.9 to 4.0 set in this application. After resistance spot welding, only a small number of extremely small LME cracks exist in the weld area. It can be seen that the maximum length of the crack is only 35 μm, and there is no large-area long crack propagation. This directly verifies that when the mass fraction ratio of Al to Si is controlled within the range required by this invention, it can effectively suppress the initiation of liquid metal embrittlement cracks caused by the penetration of molten zinc during resistance spot welding. The galvanized high-strength steel has stable and excellent resistance to liquid metal embrittlement.

[0083] Figure 7 A scanning electron microscope (SEM) image of the LME crack in a resistance spot weld of galvanized high-strength steel, provided as Comparative Example 1 of this application. According to... Figure 7It is known that the mass fraction ratio of Al to Si in the galvanized high-strength steel of Comparative Example 1 is 0.94, which is lower than the optimal composition range of 0.9 to 4.0 set in this application. After resistance spot welding, multiple LME cracks have been induced in the edge area of ​​the weld point. The number and size of the cracks are significantly larger than those of the example sample that meets the composition requirements. Some cracks have formed clear long propagation paths. This directly proves that when the mass fraction ratio of Al to Si deviates from the range required by this invention, the ability of galvanized high-strength steel to resist liquid metal embrittlement will decrease significantly. It cannot effectively inhibit the initiation and propagation of cracks caused by the penetration of molten zinc into the grain boundaries during resistance spot welding. This further verifies the necessity and rationality of the Al to Si mass fraction ratio composition design in this application for improving the LME resistance performance of galvanized high-strength steel.

[0084] Figure 8 This is a scanning electron microscope (SEM) image of the LME crack in a resistance spot weld of galvanized high-strength steel, provided as Comparative Example 2 of this application. According to... Figure 8 It is known that the Al to Si mass fraction ratio of the galvanized high-strength steel in Comparative Example 2 is 0.8, which is far below the lower limit of the composition range of 0.9 to 4.0 set in this application. After resistance spot welding, multiple large LME cracks have already appeared in the edge area of ​​the weld point, with the length of a single visible crack reaching 180 μm. The number of cracks and the maximum length are both far higher than those of the example sample that meets the composition requirements, indicating a significant problem of liquid metal embrittlement. This result directly proves that when the Al to Si mass fraction ratio is lower than the range required by this application, the galvanized high-strength steel cannot effectively suppress the penetration of molten zinc into the grain boundaries of the steel matrix during resistance spot welding, and its ability to resist liquid metal embrittlement will decrease significantly. This further confirms the rationality and necessity of controlling the Al to Si mass fraction ratio within the range of 0.9 to 4.0 in this application.

[0085] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages: This invention provides a galvanized high-strength steel resistant to liquid metal embrittlement. By optimizing the mass fraction ratio of Al to Si in the galvanized high-strength steel matrix, controlling the Al to Si mass fraction ratio within the range of 0.9 to 4.0, the penetration of liquid zinc into the grain boundaries at high welding temperatures is effectively suppressed. This technical solution significantly reduces the susceptibility of galvanized high-strength steel to liquid metal embrittlement, while improving coating quality and microstructure. The prepared galvanized high-strength steel has a tensile strength greater than 980 MPa and a yield strength greater than 700 MPa, possessing both high strength and excellent crack resistance, making it particularly suitable for resistance spot welding connections in automotive bodies.

[0086] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed in this application.

Claims

1. A galvanized high-strength steel resistant to liquid metal brittleness, characterized in that, The chemical composition of the galvanized high-strength steel, by mass fraction, is as follows: C: 0.05%~0.60%, Al: 0.08%~3.00%, Si: 0.10%~1.75%, Mn: 1.0%~5.0%, Cr: 0.20%~1.65%, Nb: 0.01%~1.05%, P≤0.02%, S≤0.007%, N≤0.006%, Cu: 0.01%~0.06%, B: 0.001%~0.003%, with the remainder being Fe and unavoidable impurities; The mass fraction ratio of Al to Si is 0.9 to 4.

0.

2. The galvanized high-strength steel according to claim 1, characterized in that, The mass fraction of C is 0.05% to 0.40%, the mass fraction of Al is 0.40% to 2.30%, and the mass fraction of Si is 0.20% to 1.25%.

3. The galvanized high-strength steel according to claim 1 or 2, characterized in that, The mass fraction ratio of Al to Si is 2.0 to 4.

0.

4. The galvanized high-strength steel according to claim 1, characterized in that, The microstructure of the galvanized high-strength steel, by volume fraction, comprises: ferrite: 10%~45%, martensite: 40%~70%, and retained austenite: 3%~12%.

5. The galvanized high-strength steel according to claim 1, characterized in that, The galvanized high-strength steel has a hot-dip galvanized layer on its surface, and an Fe-Zn alloying layer is present between the hot-dip galvanized layer and the steel substrate.

6. The galvanized high-strength steel according to claim 1, characterized in that, The galvanized high-strength steel meets at least one of the following properties: tensile strength ≥ 980 MPa, yield strength ≥ 700 MPa, elongation after fracture A 80 ≥12%.

7. A method for preparing galvanized high-strength steel according to any one of claims 1 to 6, characterized in that, The method includes: Molten steel having the chemical composition described in any one of claims 1 to 6 is continuously cast to obtain a billet; The billet is subjected to hot rolling, pickling, cold rolling and hot-dip galvanizing in sequence to obtain galvanized steel coil; The galvanized steel coil is heat-treated in a heat treatment furnace with a temperature of 70℃~350℃ and a dew point temperature of -55℃~-35℃ for 20min~60min, and then coiled to obtain galvanized high-strength steel.

8. The method according to claim 7, characterized in that, The hot-dip galvanizing bath temperature is 440℃~470℃, and the mass fraction of Al in the bath is 0.005%~0.35%.

9. An application of the galvanized high-strength steel according to any one of claims 1 to 5, characterized in that, The galvanized high-strength steel is used for resistance spot welding connections of automotive body structural components.

10. The application according to claim 9, characterized in that, The resistance spot welding uses a welding current of 8kA to 12kA, a welding time of 200ms to 400ms, and an electrode pressure of 3kN to 5kN.